Trends in LVAD Placements and Outcomes: A Nationwide Analysis Using the National Inpatient Sample and National Readmissions Database - Vivek Joseph Varughese; Vignesh Krishnan Nagesh; Hadrian Hoang-Vu Tran; Nikita Wadhwani; Audrey Thu; Simcha Weissman; Adam Atoot (Medical Sciences, 2025)
Background: Aim of the study is to analyze the trends and outcomes in Left Ventricular Assist Device (LVAD) placements between the years 2016 and 2022 using the National Inpatient Sample (NIS). Methods: Using the NIS for the years 2016–2022, we identified the total number of LVAD placements using the PCS 10 code 02HA0QZ. In-hospital outcomes and healthcare resource utilization burden were assessed. Stratification of outcomes with Extracorporeal Membrane Oxygenation (ECMO) support were performed for the years 2018–2022. Outcome analysis variance in admissions requiring ECMO support was performed using multivariate regression analysis. A two tailed p-value < 0.05 was used to determine statistical significance. Results: A general decreasing trend was observed in the total number of LVAD placements, with 852 total admissions requiring LVAD placements identified in 2016 compared to 665 in 2022. The admissions for LVAD placements requiring ECMO support had an increasing trend, with 2.21% of admissions needing ECMO support in 2018 compared to 12.18% in 2018. After multivariate regression analysis, the association between all-cause mortality during the hospital stay for LVAD placements and requirement of ECMO was found to be significant, with an odds ratio of 2.34 (1.83–4.42, p-value: 0.001). Conclusions: A general decreasing trend in LVAD placements was observed between 2016 and 2022. All-cause mortality and hospital charges during the admission had a stable trend over the years. The requirement of ECMO support had an increasing trend from 2018 to 2022. Requirement of ECMO support during the admissions for LVAD placements had a statistically significant association with all-cause mortality during the admission. A 11.50% readmission rate was observed in the 30 days following discharge, with heart failure being the major cause of readmission.